Green finance and carbon intensity in OECD economies–mediating roles of industrial structure upgrading and green technology innovation - Yang, Jiajia; Deng, Wei; Kharuddin, Saira (SAGE Publications Inc., 2026)
Green finance, industrial structure upgrading (ISU), and green technology innovation (GTI) are anticipated to diminish carbon intensity and boost sustainable growth. Nevertheless, there are varying perspectives on the effectiveness of green finance in reducing carbon emissions within OECD countries, and the underlying mechanisms remain unclear. Therefore, this study investigates the relationship between green finance and carbon intensity, with a particular focus on the mediating roles of ISU and GTI, using panel data from 31 OECD countries spanning 2003 to 2022. Methodologically, this study employs multiple econometric techniques, including ordinary least squares (OLS), the panel-corrected standard error (PCSE) method, the system generalised method of moments (GMM) model, and the instrumental variable approach. The outcomes reveal that carbon intensity has been diminished by green finance in OECD economies. Furthermore, the impact of green finance on carbon intensity is negatively mediated by ISU. Carbon intensity is not only directly minimised by green finance but also through the mediator of GTI. In addition, the effects of green finance on lowering carbon intensity are particularly pronounced in low-income and high-carbon countries. Lastly, this study provides policy recommendations aimed at enhancing carbon reduction efforts in OECD and developing economies.